Characterization of ZnO thin film grown on c-plane substrates by MO-CVD: Effect of substrate annealing temperature, vicinal-cut angle and miscut direction. (September 2015) - Boukadhaba, M.A.; Fouzri, A.; Sallet, V.; Hassani, S.S.; Amiri, G.; Lusson, A.; Oumezzine, M.
Highlights: Different substrate surface pretreatments were carried out. c -axis oriented ZnO films were deposited on α-Al2 O3 (0 0 0 1) substrates by MOCVD. Annealing substrate temperature improved the structural and optical property of ZnO film. High-quality ZnO films deposited on vicinal-cut angle α = 0.25° toward the m-plane. Abstract: The annealing effects of c-plane sapphire (α-Al2 O3 ) substrate with a nominally vicinal-cut angle α ( α < 0.1°, α = 0.25° toward the m-plane ( 1 0 1 ¯ 0 ) and α = 0.25° toward the a-plane ( 1 1 2 ¯ 0 ) ) on the quality of epitaxial ZnO films grown by metal organic chemical vapor deposition (MO-CVD) were studied. The atomic steps formed on sapphire substrate surface by annealing at high temperature were analyzed by atomic force microscopy (AFM). The annealing and the miscut direction of sapphire substrate on the microstructural and optical properties for ZnO films were examined by high resolution X-ray diffraction (HR-XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM) and photoluminescence spectroscopy (PL). Experimental results indicate that the film quality is strongly affected by annealing treatment and miscut direction of the sapphire substrate. X-ray diffraction study revealed that all films exhibit a wurtzite phase and have a c -axis orientation. ZnO films deposited on sapphire substrate ( α < 0.1° and α = 0.25° toward the m-plane ( 1 0 1 ¯ 0 ), annealed substrate at 1100 °C), exhibit a low quantity of defects and a quite good vertical and lateral alignment compared to other disorientation plane ( α = 0.25° toward the a-plane ( 1 1 2 ¯ 0 ), annealed substrate at 1100 °C). The Lattice parameters a and c slightly decreases for ZnO layer deposited on annealed sapphire substrate with increase the annealing substrate temperature for all samples. AFM image show significant differences between morphologies of samples depending on annealing treatment and miscut direction of substrates but no significant differences on surface roughness have been found. Sapphire annealing at 1100 °C with a nominally vicinal-cut angle α = 0.25° toward the m-plane ( 1 0 1 ¯ 0 ), provides the best optical quality of ZnO film.